Autism: making reasonable adjustments in healthcare. (2nd December 2021) - Haydon, Clair; Doherty, Mary; Davidson, Ian A
Abstract : The accompanying article set out why it is important to identify autistic people and the negative consequences of not recognising or understanding autism, including more severe illness and premature death. This article sets out what clinicians can do to help reduce those negative consequences by making 'reasonable adjustments' in any healthcare service in which they work.